Low-temperature co-fired ceramic composite material with high thermal expansion coefficient, preparation method thereof and electronic component

By adjusting the ratio of SiO2, Al2O3 and ZrO2, a high thermal expansion coefficient and low temperature co-fired ceramic composite material was developed, which solved the shortcomings of ceramic packaging materials in terms of thermal expansion and dielectric properties, and achieved good matching with PCB boards and efficient dielectric properties.

CN119751035APending Publication Date: 2025-04-04SHENZHEN SUNLORD ELECTRONICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411842210.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing ceramic packaging materials have shortcomings in thermal expansion performance, dielectric performance and environmental friendliness, resulting in poor matching with PCB boards, which can easily cause thermal mismatch and product deformation.

Method used

A high thermal expansion coefficient low temperature co-fired ceramic composite material was developed. By adjusting the ratio of SiO2, Al2O3 and ZrO2, the thermal expansion coefficient of the material is controlled to make it close to the thermal expansion coefficient of the PCB board, and B2O3, K2O and Na2O are added to improve dielectric performance and sintering density.

Benefits of technology

The thermal expansion coefficient of ceramic composite materials is achieved close to that of PCB boards, reducing the occurrence of thermal mismatch, improving dielectric properties and structural strength, and enhancing the environmental friendliness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751035A_ABST
    Figure CN119751035A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to a high-thermal-expansion-coefficient low-temperature co-fired ceramic composite material, a preparation method thereof and an electronic component. The invention discloses a low-temperature co-fired ceramic composite material. The low-temperature co-fired ceramic composite material is prepared by mixing glass and ceramic, comprising the following components in percentage by mass: 30 to 50 percent of SiO2, 5 to 10 percent of CaO, 10 to 20 percent of Al2O3, 20 to 30 percent of ZrO2, 5 to 10 percent of B2O3, 1 to 2 percent of K2O and 1 to 2 percent of Na2O. The low-temperature co-fired ceramic composite material with the high thermal expansion coefficient is better matched with a PCB material, the dielectric constant of the low-temperature co-fired ceramic composite material with the high thermal expansion coefficient is smaller than 6.5, the dielectric loss is smaller than 0.002, the bending strength is larger than 150 MPa, welding spots and product deformation and cracking caused by thermal mismatch caused by thermal expansion and cold contraction in the welding process can be reduced, and the product quality is improved. And the problem of product failure is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of low-temperature co-fired ceramic materials, and in particular to a low-temperature co-fired ceramic composite material with a high thermal expansion coefficient, a preparation method thereof, and an electronic component. Background Art

[0002] The rapid development of modern electronic information technology has greatly promoted the development of electronic devices towards high performance, high reliability, low cost, miniaturization, portability and popularization. The development of IC (integrated circuit) has greatly improved the density of circuits. The circuit function density carried by an IC chip is several orders of magnitude larger than that of traditional printed circuits, especially VLSI (very large scale integrated circuit). The advantages of IC can only be achieved when it is integrated with other resistors, capacitors, multi-chip hybrid circuits, etc., so the circuit still needs to be assembled, and sometimes the IC itself needs to be packaged into a device to cope with harsh environments. IC packaging has long developed into an independent industry internationally, and together with IC design, IC manufacturing and chip testing, it constitutes the four pillars of the semiconductor industry. my country has independently developed a number of new packaging structures, but overall, my country's electronic packaging industry is still quite backward.

[0003] The ball grid array (BGA) technology that emerged in the 1990s is a surface-mount package that plants ball pins in an array under a substrate and mounts a chip on the substrate. BGA packaging is mainly divided into PBGA (plastic-encapsulated BGA) and CBGA (ceramic BGA) according to the type of substrate. Compared with plastic, the advantages of ceramic substrate materials are: (1) lower dielectric constant and loss, which can improve the signal transmission rate; (2) high resistivity, ensuring the insulation between signal lines; (3) ceramic materials have relatively high thermal conductivity, which can better dissipate heat when making multi-layer substrates; (4) easier to plant balls than plastic, with a large number of I / Os; (5) good stability, which can be used in places with high requirements for airtightness; (6) passive device integration can be achieved in multi-layer ceramic substrates made using thick film hybrid circuit technology; thus, the packaging density is higher than that of PBGA. However, there are still a series of problems in the ceramic packaging materials commonly used today: poor thermal matching performance between materials and electrode materials and chips, poor serialization of thermal expansion coefficients of substrate materials, and environmental pollution caused by raw materials. Summary of the invention

[0004] The present application discloses a low-temperature co-fired ceramic composite material with a high thermal expansion coefficient, a preparation method thereof, and an electronic component. The low-temperature co-fired ceramic composite material mainly comprises low-temperature cristobalite SiO 2 Mainly, by adding appropriate amount of Al 2 O 3 , which can inhibit the low-temperature cristobalite SiO 2 The precipitation of ZrO 2, promoting low-temperature cristobalite SiO 2 The precipitation is adjusted to adjust the degree of crystallization; the present application adjusts Al 2 O 3 With ZrO 2 By adjusting the ratio between the two, the degree of crystallization can be adjusted to control the thermal expansion coefficient of the material, so that the thermal expansion coefficient of the low-temperature co-fired ceramic composite material is closer to that of the PCB board and meets the requirements of low dielectric constant, low dielectric loss and high strength.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The first object of the present application is to provide a low temperature co-fired ceramic composite material with a high thermal expansion coefficient, which is composed of a mixture of glass and ceramic;

[0007] The high thermal expansion coefficient low temperature co-fired ceramic composite material includes the following components in percentage by weight: SiO 2 : 30~50%, CaO: 5~10%, Al 2 O 3 :10~20%,ZrO 2 :20~30%,B 2 O 3 :5~10%,K 2 O: 1-2%, Na 2 O: 1~2%.

[0008] In some specific embodiments, the following components are included in percentage by weight:

[0009] SiO 2 : 40~45%, CaO: 6~8%, Al 2 O 3 :11~17%,ZrO 2 :21~29%,B 2 O 3 :6~9%,K 2 O: 1.1-1.9%, Na 2 O: 1.1~1.9%.

[0010] In some specific embodiments, the following components are included in percentage by weight:

[0011] SiO 2 :40%,CaO:8%,Al 2 O 3 : 10%, ZrO 2 : 30%, B 2 O 3 : 9%, K 2 O: 1.5%, Na 2 O: 1.5%.

[0012] In some specific embodiments, the glass composition includes the following components in percentage by weight: SiO 2 : 50~70%, CaO: 10~20%, Al 2 O 3 :0~5%,ZrO 2 :0~5%,B 2 O 3 :10~20%,K 2 O: 1-3%, Na 2 O: 1~3%.

[0013] In some specific embodiments, the low temperature co-fired ceramic composite material satisfies:

[0014] Thermal expansion coefficient>10ppm / ℃;

[0015] and / or dielectric loss < 0.002;

[0016] And / or the low temperature co-fired ceramic composite material can resist repeated thermal shock for more than 300 times at RT→300°C (5°C / min).

[0017] In some specific embodiments, the thermal expansion coefficient of the low-temperature co-fired ceramic composite material is 10-18 ppm / °C.

[0018] The second object of the present application is to provide a method for preparing a low temperature co-fired ceramic composite material, comprising the following steps:

[0019] Mix the following glass raw materials according to the mass percentage: SiO 2 : 50~70%, CaO: 10~20%, Al 2 O 3 :0~5%,ZrO 2 :0~5%,B 2 O 3 :10~20%,K 2 O: 1-3%, Na 2 O: 1-3%, glass is melted at 1500℃ / 2h, and then water quenched, dried and ball-milled to make glass powder;

[0020] Then add the above glass powder and 10-20% Al 2 O 3 and 20~30% ZrO 2 The ceramic powder is mixed to make a low-temperature co-fired ceramic composite material.

[0021] In some specific embodiments, the sintering temperature of the composite material is 800° C. / 1 h.

[0022] The third object of the present application is to provide an electronic component, comprising the low-temperature co-fired ceramic composite material as described above or the low-temperature co-fired ceramic composite material prepared by the preparation method as described above.

[0023] In some specific embodiments, the electronic components include LTCC substrates and / or radio frequency components.

[0024] The beneficial effects of this application are:

[0025] Provided is a low temperature co-fired ceramic composite material with a high thermal expansion coefficient, comprising 10-20% Al 2 O 3 and 20-30% ZrO 2 , which makes the thermal expansion coefficient of the low-temperature co-fired ceramic composite material greater than 10ppm / ℃, which is close to the thermal expansion coefficient of the PCB board (10-18ppm / ℃). Therefore, the low-temperature co-fired ceramic composite material has a better matching with the PCB board material. The dielectric constant of the high thermal expansion coefficient low-temperature co-fired ceramic composite material is less than 6.5, the dielectric loss is less than 0.002, and the bending strength is greater than 150MPa. It has the characteristics of low loss, high expansion, high strength, can be sintered at low temperature to be dense, and contains microcrystallizable glass. It can reduce the thermal mismatch caused by thermal expansion and contraction during the welding process, which causes the solder joints and product deformation and cracking, leading to the problem of product failure.

[0026] Provided is a method for preparing a low-temperature co-fired ceramic composite material with a high thermal expansion coefficient, which has a simple composition and is easy to sinter.

[0027] Provided is an electronic component having the same beneficial effects as the above-mentioned high thermal expansion coefficient low temperature co-fired ceramic composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0029] Figure 1 SEM image of the surface of the low temperature co-fired ceramic composite material with high thermal expansion coefficient in Example 3 of the present application;

[0030] Figure 2 SEM image of the cross section of the low temperature co-fired ceramic composite material with high thermal expansion coefficient in Example 3 of the present application;

[0031] Figure 3 Phase diagram of the high thermal expansion coefficient low temperature co-fired ceramic composite material of Example 3 of the present application;

[0032] Figure 4 A relationship diagram of thermal expansion coefficients of a low temperature co-fired ceramic composite material with a high thermal expansion coefficient according to Example 3 of the present application;

[0033] Figure 5Example 3 of the present application shows that the high thermal expansion coefficient low temperature co-fired ceramic composite material is used to test the high thermal expansion coefficient sample diagram;

[0034] Figure 6 The finished product of the low-temperature co-fired ceramic composite material with high thermal expansion coefficient in Example 3 of the present application after repeated thermal shock resistance at RT→300°C (5°C / min) for 300 times. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0036] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0038] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0039] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. The manufacturer or concentration is not specified, and they are all analytically pure raw materials or reagents that can be routinely obtained. As long as the expected effect can be achieved, there is no particular restriction. The instruments and equipment used in the present embodiment are all purchased from major manufacturers in the market. As long as the expected effect can be achieved, there is no particular restriction. If specific techniques or conditions are not specified in the present embodiment, the techniques or conditions described in the literature in this area or according to the product specification are carried out.

[0040] Terminology explanation:

[0041] Coefficient of thermal expansion: Description The coefficient of thermal expansion is a physical quantity that measures the degree of change in volume or length of a material when the temperature changes;

[0042] LTCC: Low temperature co-fired ceramic;

[0043] CBGA: ball-bonded array packaging technology;

[0044] At present, the difference in thermal expansion coefficient between ceramic and PCB is large, so the thermal mismatch caused by thermal expansion and contraction causes solder joints and product deformation and cracking, leading to product failure. The requirements of low dielectric constant, low dielectric loss and high strength are met; in order to further reduce the difference in thermal expansion coefficient between ceramic composite materials and PCB boards, the present application provides a Figures 1-2 The high thermal expansion coefficient low temperature co-fired ceramic composite material shown is composed of a mixture of glass and ceramic;

[0045] The high thermal expansion coefficient low temperature co-fired ceramic composite material includes the following components in percentage by weight: SiO 2 : 30~50%, CaO: 5~10%, Al 2 O 3 :10~20%,ZrO 2 :20~30%,B 2 O 3 :5~10%,K 2 O: 1-2%, Na 2 O: 1~2%.

[0046] When quartz silicon dioxide is at 250-290℃, β-cristobalite transforms to α-cristobalite, that is, high-temperature cristobalite SiO 2 To low temperature cristobalite SiO 2 Transformation, the volume expansion rate can reach 1.5%. Using this characteristic of cristobalite to design a high thermal expansion coefficient low-temperature co-fired ceramic composite material, the ceramic composite material needs to precipitate a certain proportion of cristobalite phase (SiO 2 ), so that the thermal expansion coefficient of the ceramic composite material is closer to that of the PCB board.

[0047] It can be understood that the above components can be obtained by analyzing the composition of the high thermal expansion coefficient low temperature co-fired ceramic composite material.

[0048] It is understandable that SiO 2 It is the main system of low-temperature co-fired ceramic composite materials with high thermal expansion coefficient; CaO is used to promote sintering densification and improve the dielectric properties of the material; Al 2 O 3 As an inhibitor, it inhibits SiO 2 Precipitation of ZrO 2 As a promoter, it promotes the transformation of β-cristobalite to α-cristobalite and increases the thermal expansion coefficient of ceramic composite materials; B 2 O 3 As flux, it improves the fluidity and sintering density of materials; K 2 O and Na 2 O can be used to reduce the softening point of ceramic composites, promote sintering densification, accelerate the formation of calcium feldspar phase, and reduce dielectric loss.

[0049] Without adding Al 2 O 3 , which will lead to a larger thermal expansion coefficient of the ceramic composite material, which can reach 15.5ppm / ℃, and a higher failure rate of PCB at high and low temperature impact, reaching 10%; such as Al 2 O 3 If too much is added, the thermal expansion coefficient of the ceramic composite material will be smaller, less than 10ppm / ℃, and the high and low temperature impact failure rate of the PCB will be higher, reaching 90%.

[0050] Specifically, Al 2 O 3 The content of ZrO is kept within the range of 10-20%. 2 The content of is maintained in the range of 20-30%, ensuring that the ceramic composite material has the properties of low dielectric constant, low dielectric loss and high structural strength.

[0051] Specifically, SiO 2 The range is 30-50%, for example SiO 2 The mass percentage of SiO is any value within the range of 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, and 50%; 2 The range of SiO is 30-50% (including the end point value), ensuring that the ceramic composite material has sufficient mechanical strength and chemical stability. 2 Too much content will make the ceramic composite material too brittle and hard.2 If the content is too small, it will not provide the necessary structural support for the ceramic composite material.

[0052] Specifically, the range of CaO is 5 to 10%, for example, the mass percentage of CaO is any value within the range of 5%, 6%, 7%, 8%, 9%, and 10%; the range of CaO is 5 to 10% (including the endpoint values), which helps to reduce the sintering temperature and increase the density of the material. Too much CaO content will increase the dielectric loss, and too little CaO content may not be sufficient to effectively improve the dielectric properties.

[0053] Specifically, Al 2 O 3 The range is 10-20%, for example, Al 2 O 3 The mass percentage of Al is any value within 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. 2 O 3 The range is 10-20% (including the endpoint value), which can inhibit SiO 2 Precipitation of Al2O3 to avoid excessive precipitation of α-cristobalite and excessive thermal expansion of ceramic composite materials; 2 O 3 Too high a content of Al will reduce the amount of transformation from β-cristobalite to α-cristobalite, resulting in a low thermal expansion coefficient; 2 O 3 If the content is too low, thermal expansion cannot be effectively controlled.

[0054] Specifically, ZrO 2 The range is 20-30%, for example, ZrO 2 The mass percentage of ZrO is any value within 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%; 2 The range is 20-30% (including the endpoint value), which can promote the transformation of β-cristobalite to α-cristobalite and improve the thermal expansion coefficient of low-temperature co-fired ceramic composite materials; if ZrO 2 If the content is too high, the brittleness of the material may increase; if the ZrO2 content is insufficient, the thermal expansion coefficient of the ceramic composite material may not meet the requirements.

[0055] Specifically, B 2 O 3 The range is 5-10%, for example, B 2 O 3 The mass percentage of B is any value within 5%, 6%, 7%, 8%, 9% and 10%; 2 O 3The range is 5 to 10% (including the endpoint value), B 2 O 3 Can improve the fluidity and sintering density of ceramic composite materials; B 2 O 3 Too high a content will weaken the mechanical strength of the material. 2 O 3 A lower content is not conducive to densification during sintering.

[0056] Specifically, K 2 O ranges from 1 to 2%, for example, K 2 The mass percentage of O is any value within the range of 1%, 1.5%, or 2%, and can be within the range of 1 to 2% (including the endpoint values). 2 O ranges from 1 to 2%, for example, Na 2 The mass percentage of O is any value within the range of 1%, 1.5%, or 2%, and can be within the range of 1 to 2% (including the endpoint values). 2 O and Na 2 O can lower the softening point of glass, promote sintering densification, accelerate the formation of calcium feldspar phase, and reduce dielectric loss.

[0057] When SiO 2 、CaO、Al 2 O 3 、ZrO 2 , B 2 O 3 , K 2 O and Na 2 When O falls within the above range, the thermal expansion coefficient of the ceramic composite material is close to that of the PCB board, the dielectric loss is small, and the high and low temperature impact failure rate of the PCB can reach 0%.

[0058] In some embodiments, the following components are included in percentage by weight:

[0059] SiO 2 : 40~45%, CaO: 6~8%, Al 2 O 3 :11~17%,ZrO 2 :21~29%,B 2 O 3 :6~9%,K 2 O: 1.1-1.9%, Na 2 O: 1.1~1.9%.

[0060] It is understandable that by adjusting SiO 2 、CaO、Al 2 O 3 、ZrO 2 , B2 O 3 , K 2 O、Na 2 The ratio of O can adjust the content of β-cristobalite and α-cristobalite, thereby optimizing the thermal expansion coefficient, dielectric constant and loss and strength of the low-temperature co-fired ceramic composite material.

[0061] In some embodiments, the following components are included in percentage by weight: SiO 2 :40%,CaO:8%,Al 2 O 3 : 10%, ZrO 2 : 30%, B 2 O 3 : 9%, K 2 O: 1.5%, Na 2 O: 1.5%. The thermal expansion coefficient of the ceramic composite material in this embodiment reaches 13.8ppm / °C, which is closest to the thermal expansion coefficient of the common PCB board (thermal expansion coefficient 14ppm / °C) on the market, so the occurrence of thermal mismatch caused by thermal expansion and contraction is minimal.

[0062] In some embodiments, the low temperature co-fired ceramic composite material satisfies:

[0063] Thermal expansion coefficient>10ppm / ℃;

[0064] And\or dielectric loss <0.002;

[0065] And\or the low temperature co-fired ceramic composite material can resist repeated thermal shock for more than 300 times at RT→300°C (5°C / min).

[0066] It can be understood that RT→300°C (5°C / min) means: starting from room temperature, heating at a rate of 5°C per minute until the target temperature of 300°C is reached and the thermal shock is repeatedly resisted 300 times.

[0067] In some embodiments, the glass includes the following components in percentage by weight: SiO 2 : 50~70%, CaO: 10~20%, Al 2 O 3 :0~5%,ZrO 2 :0~5%,B 2 O 3 :10~20%,K 2 O: 1-3%, Na 2 O: 1~3%.

[0068] It is understandable that SiO 2 Provide enough cristobalite for subsequent reactions, Al2 O 3 and ZrO 2 Adjust the precipitation degree of cristobalite and provide sufficient cristobalite SiO 2 , to ensure sufficient low-temperature quartz SiO 2 Precipitation.

[0069] Specifically, SiO 2 The range is 50-70%, for example SiO 2 The mass percentage can be any value within the range of 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, or 70%, and can be within the range of 50-70% (including the endpoint values).

[0070] Specifically, the range of CaO is 10-20%, for example, the mass percentage of CaO is any value within 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, within the range of 10-20% (including the endpoint values);

[0071] Specifically, Al 2 O 3 The range is 0-5%, for example, Al 2 O 3 The mass percentage content is any value within the range of 0%, 1%, 2%, 3%, 4%, and 5%, and can be within the range of 0 to 5% (including the endpoint values);

[0072] Specifically, ZrO 2 The range is 0-5%, for example, ZrO 2 The mass percentage content is any value within the range of 0%, 1%, 2%, 3%, 4%, and 5%, and can be within the range of 0 to 5% (including the endpoint values);

[0073] Specifically, B 2 O 3 The range is 10-20%, for example, B 2 O 3 The mass percentage content is any value within the range of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, and within the range of 10-20% (including the endpoint values);

[0074] Specifically, K 2 O ranges from 1 to 3%, for example, K 2 The mass percentage of O is any value within the range of 1%, 1.5%, 2%, 2.5%, and 3%, and can be within the range of 1 to 3% (including the endpoint values);

[0075] Specifically, Na 2 O ranges from 1 to 3%, for example, Na 2 The mass percentage of O can be any value within the range of 1%, 1.5%, 2%, 2.5%, and 3%, and can be within the range of 1 to 3% (including the endpoint values).

[0076] In some embodiments, the thermal expansion coefficient of the low-temperature co-fired ceramic composite material is 10-18 ppm / °C.

[0077] The method for preparing the above-mentioned low temperature co-fired ceramic composite material comprises the following steps:

[0078] Mix the following raw materials according to the mass percentage: SiO 2 : 50~70%, CaO: 10~20%, Al 2 O 3 :0~5%,ZrO 2 :0~5%,B 2 O 3 :10~20%,K 2 O: 1-3%, Na 2 O: 1-3%; glass is melted at 1500℃ / 2h, and then water quenched, dried and ball-milled to produce glass powder;

[0079] Then add the above glass powder and 10-20% Al 2 O 3 and 20~30% ZrO 2 The ceramic powder is mixed to produce a high thermal expansion coefficient low-temperature co-fired ceramic composite material.

[0080] It can be understood that, through the above raw material combination and preparation method, a low-temperature co-fired ceramic composite material with a thermal expansion coefficient of more than 10 ppm / °C and a dielectric loss of less than 0.002 can be prepared.

[0081] The following is a further description of a low temperature co-fired ceramic composite material and a preparation method of the present invention in combination with specific embodiments and comparative examples:

[0082] S1. According to Table 1, weigh the glass raw materials: SiO 2 : 50~70%, CaO: 10~20%, Al 2 O 3 :0~5%,ZrO 2 :0~5%,B 2 O 3 :10~20%,K 2 O: 1-3%, Na 2O: 1-3%; fully mix in a ball mill, ball milling parameters, speed: 250rpm / min, time 4 hours, to obtain a glass mixture;

[0083] S2. Glass melting: melting the glass mixture in a platinum crucible at a temperature of 1500°C for 2 hours; and introducing the high-temperature molten glass into water to obtain transparent glass slag;

[0084] S3, composite mixing: the molten glass slag in S2 is ball-milled and crushed, and then the remaining amount (by mass percentage) of Al 2 O 3 and ZrO 2 (i.e. ceramic powder), mixed in a ball mill, ball milling parameters: speed: 250rpm / min, time 4 hours, to obtain glass powder;

[0085] Among them, in this step, Al 2 O 3 and ZrO 2 The amount of addition is based on the total content of the specific examples and comparative examples in Table 1 minus the Al in step S1 2 O 3 With ZrO 2 The corresponding amount added;

[0086] S4, molding: granulate the powder in step S3 under 5% PVA glue; dry press molding under 6T pressure, the sample length is 30mm, the width is 4.75mm, and the height is 3.75mm, to obtain a green sample;

[0087] S5, sintering: the green sample in step S4 is debinded at 450°C, sintered at 900°C for 2 hours, and cooled naturally to obtain a sintered sample; Figure 5 The ceramic composite semi-finished product shown;

[0088] S6, the powder of step S3 is pulped and cast, silver paste is printed (the printing silver paste area is 80*70mm) on the sintered sample, silver paste is laminated (thickness is 1mm), warm water press (5000MPa), cut into small pieces with a size of 100*100mm, debind at 450℃, sintered at 800℃ for 2 hours, and cooled naturally;

[0089] S7, then electroplate the ceramic sheet and solder it to the PCB board using tin. Figure 6 The ceramic composite material.

[0090] Table 1

[0091]

[0092] The preparation methods of the ceramic composite materials in all the examples and comparative examples are consistent. The performance of the ceramic composite materials prepared in the examples and comparative examples was tested, and the relevant results are summarized in Table 2;

[0093] Performance testing, including:

[0094] (1) Sintered density, Archimedes drainage method (sample size: 14 mm*4 mm cylinder);

[0095] (2) Dielectric constant, high frequency test (1G~20GHz) by resonant cavity method (sample size: 14mm*4mm cylinder);

[0096] (3) Dielectric loss, resonant cavity method high frequency test (1G ~ 20GHz) (sample size: 14mm*4mm cylinder);

[0097] (4) Thermal expansion coefficient, ejector method test (sample size: 50*5*5mm long strip);

[0098] (5) Flexural strength, three-point bending method, sample size: 50*4*3mm, test span: 30mm;

[0099] (6) PCB high and low temperature impact failure rate, using a fast temperature change box + microscope, sample size 100mm*100mm, test heating and cooling rate 20℃ / min, and observe whether the welding position is detached through a microscope;

[0100] Table 2

[0101]

[0102]

[0103] Referring to Table 2, it can be seen that comparative example 1 has failure under impact, which does not meet the requirements; the dielectric loss of comparative example 2 material is relatively large 0.005, the thermal expansion coefficient is low, which is far from the thermal expansion coefficient of the PCB board (10-18ppm / ℃), and the high and low temperature impact failure rate is 90%, which does not meet the requirements.

[0104] The dielectric loss coefficient of Examples 1 to 5 ranges from 0.0012 to 0.003. The lower the dielectric loss coefficient, the smaller the energy loss of the material in the AC electric field, which can reduce the attenuation during signal transmission, improve the transmission efficiency and quality of the signal, and the ceramic composite materials made therefrom generate less heat and have greater stability.

[0105] The chemical compositions of the ceramic composite materials of Examples 1 to 6 and Comparative Examples 1 to 2 were tested, and the results are shown in Table 3.

[0106] Table 3

[0107]

[0108]

[0109] See also Figure 1 , Figure 2 The ceramic composite material prepared in the present application has good surface and cross-sectional density in microscopic morphology;

[0110] See also Figure 3 The ceramic composite material prepared in this application has a baddeleyite phase (ZrO 2 ) and cristobalite phase (SiO 2 ) two physical phases.

[0111] The thermal expansion coefficient range of Examples 1 to 5 is 13.8 to 10.4 ppm / °C, which is relatively close to the thermal expansion coefficient of the PCB board (10 to 18 ppm / °C), and has better matching with the PCB board material. It can reduce the problem of thermal mismatch caused by thermal expansion and contraction during the welding process, which may cause deformation and cracking of solder joints and products, leading to product failure.

[0112] In summary, it can be seen that the low-temperature co-fired ceramic composite material prepared by this preparation method has the characteristics of low loss, high expansion, high strength, can be sintered at low temperature to be dense, and contains microcrystallizable glass. The low-temperature co-fired ceramic composite material prepared by this preparation method has excellent comprehensive performance, simple composition, and is easy to sinter, so it is more suitable for matching packaging with high expansion substrate PCB.

[0113] Another aspect of the present application provides an electronic component, wherein the low-temperature co-fired ceramic composite material in any one of the above embodiments or the low-temperature co-fired ceramic composite material prepared by the preparation method in any one of the above embodiments is used to manufacture the electronic component;

[0114] Specifically, the low temperature co-fired ceramic composite material described in the present application is used to produce LTCC substrates and / or radio frequency components through existing processes.

[0115] In some embodiments, the electronic components include LTCC substrates and / or radio frequency components.

[0116] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A low temperature co-fired ceramic composite material with high thermal expansion coefficient, characterized in that: It is composed of a mixture of glass and ceramic; The invention comprises the following components in percentage by mass: SiO2: 30-50%, CaO: 5-10%, Al2O3: 10-20%, ZrO2: 20-30%, B2O3: 5-10%, K2O: 1-2%, and Na2O: 1-2%.

2. The high thermal expansion coefficient low temperature co-fired ceramic composite material according to any one of claims 1, characterized in that: Includes the following components in percentage by mass: SiO2: 40~45%, CaO: 6~8%, Al2O3: 11~17%, ZrO2: 21~29%, B2O3: 6~9%, K2O: 1.1~1.9%, Na2O: 1.1~1.9%.

3. The high thermal expansion coefficient low temperature co-fired ceramic composite material according to claim 1, characterized in that: Includes the following components in percentage by mass: SiO2: 40%, CaO: 8%, Al2O3: 10%, ZrO2: 30%, B2O3: 9%, K2O: 1.5%, Na2O: 1.5%.

4. The high thermal expansion coefficient low temperature co-fired ceramic composite material according to claim 1, characterized in that: The glass composition includes the following components in percentage by mass: SiO2: 50-70%, CaO: 10-20%, Al2O3: 0-5%, ZrO2: 0-5%, B2O3: 10-20%, K2O: 1-3%, and Na2O: 1-3%.

5. The high thermal expansion coefficient low temperature co-fired ceramic composite material according to any one of claims 1 to 4, characterized in that: The high thermal expansion coefficient low temperature co-fired ceramic composite material meets the following requirements: Thermal expansion coefficient>10ppm / ℃; And\or dielectric loss <0.002; And\or the low temperature co-fired ceramic composite material can resist repeated thermal shock for more than 300 times at RT→300°C (5°C / min).

6. The high thermal expansion coefficient low temperature co-fired ceramic composite material according to any one of claims 1 to 4, characterized in that: The thermal expansion coefficient of the high thermal expansion coefficient low temperature co-fired ceramic composite material is 10-18 ppm / °C.

7. The method for preparing a low temperature co-fired ceramic composite material with high thermal expansion coefficient according to any one of claims 1 to 6, characterized in that: The following steps are involved: The following glass raw materials are mixed according to the mass percentage components: SiO2: 50-70%, CaO: 10-20%, Al2O3: 0-5%, ZrO2: 0-5%, B2O3: 10-20%, K2O: 1-3%, Na2O: 1-3%; the glass is melted at 1500°C / 2h, and the glass powder is made through water quenching, drying and ball milling; The glass powder is then mixed with ceramic powder containing 10-20% Al2O3 and 20-30% ZrO2 to produce a low temperature co-fired ceramic composite material with a high thermal expansion coefficient.

8. The method for preparing a low temperature co-fired ceramic composite material with a high thermal expansion coefficient as claimed in claim 7, characterized in that: The sintering temperature is 800° C. / 1 h.

9. An electronic component, characterized in that: The invention comprises the high thermal expansion coefficient low temperature co-fired ceramic composite material as claimed in any one of claims 1 to 6 or the high thermal expansion coefficient low temperature co-fired ceramic composite material prepared by the preparation method as claimed in any one of claims 7 to 8.

10. The electronic component according to claim 9, characterized in that: The electronic components include LTCC substrates and / or radio frequency components.

Citation Information

Cited By

  • Microwave dielectric material, preparation method thereof and electronic component

    CN121449409A